A Critical Review of the Book The Nature of Mystical Knowledge - Zeynab Shariatnia; Hadi Vakili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article seeks to critique and review the book “The Essence of Mystical Knowledge” by Massoud Ismaili. In this book, the writer has tried to examine the nature of mystical knowledge in two Islamic and western spaces taking a look at the comparative approach in a comprehensive system. If the criterion for our assessment is the degree to which the outer succeeds and does not succeed in expressing the issue, we can say that this book has worked well in the field of the philosophy of mysticism, and despite some of the formal and material shortcomings in it, the book seems to be acceptable.